Enriching the endophytic bacterial microbiota of Ginkgo roots - Zhang, Shuangfei; Sun, Chongran; Liu, Xueduan; Liang, Yili (Frontiers in Microbiology, 2023)
Bacterial endophytes of Ginkgo roots take part in the secondary metabolic processes of the fossil tree and contribute to plant growth, nutrient uptake, and systemic resistance. However, the diversity of bacterial endophytes in Ginkgo roots is highly underestimated due to the lack of successful isolates and enrichment collections. This study collected 455 unique bacterial isolates representing 8 classes, 20 orders, 42 families, and 67 genera from 5 phyla: Actinobacteria, Bacteroidetes, Firmicutes, Proteobacteria, and Deinococcus-Thermus, using simply modified media (a mixed medium without any additional carbon sources [MM] and two others separately added starch [GM] and glucose [MSM]). A series of plant growth-promoting endophytes had multiple representatives within the culture collection. Moreover, we investigated the impact of refilling carbon sources on enrichment outcomes. Roughly 77% of the natural community of root-associated endophytes were predicted to have the successfully cultivated possibility based on a comparison of 16S rRNA gene sequences between the enrichment collections and the Ginkgo root endophyte community. The rare or recalcitrant taxa in the root endosphere were mainly associated with Actinobacteria, Alphaproteobacteria, Blastocatellia, and Ktedonobacteria. By contrast, more OTUs (0.6% in root endosphere) significantly enriched in MM than GM and MSM. We further found that the bacterial taxa of the root endosphere had strong metabolisms with the representative of aerobic chemoheterotrophy, while the functions of the enrichment collections were represented by sulfur metabolism. In addition, the cooccurrence network analysis suggested the substrate supplement could significantly impact bacterial interactions within the enrichment collections. Our results support that the enrichment is better to assess cultivable potential and the interspecies interaction as well as increase the detection/isolation of certain bacterial taxa. Taken together, this study will deepen our knowledge of the indoor endophytic culture and provide important insights into the substrates-driven enrichment.